(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To assess the current status of the health workforce at Chi Linh Medical Center, Hai Duong province in the period 2022-2024 in order to provide an evidence for developing strategies to attract, retain, and develop the health workforce. Methods: A cross-sectional descriptive study using secondary data retrospectively collected from personnel records at Chi Linh Medical Center during 2022-2024. Results: The total number of health staff increased from 244 in 2022 to 270 in 2024. Females accounted for a high proportion (77%), with the majority aged 31-50 years (72.6%). In terms of professional composition, nurses got the highest proportion (52-53%), followed by medical doctors (19.6- 0.5%) and pharmacists (6.3-6.6%). The proportion of staff with postgraduate qualifications remained low (11-12.8%). An imbalance in workforce structure according to Circular 08/2007/TTLT-BYT-BNV of Ministry of Health was observed with a surplus in clinical staff and shortages in paraclinical and pharmaceutical personnel. Between 2022 and 2024, there were 30 resignations, of which 73.3% were due to retirement, 13.3% due to job transfers, and 13.3% due to voluntary resignation. Conclusion: The health workforce at Chi Linh Medical Center showed an upward trend in quantity but remained insufficient and imbalanced in certain departments, particularly paraclinical and pharmaceutical services. Enhancing the quality and structure of the workforce, along with appropriate policies to attract and retain staff, is essential to ensure the quality of healthcare services in the coming period.